PENGARUH KUALITAS PRODUK, HARGA, DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN YANG DIMODERASI KEPUASAN PADA KONSUMEN WARUNG MAKAN JODHO BEKONANG - Setyaningsih Sri Utami, Enggar Wicakso, Suprihatmi Sri Wardiningsih & (Universitas Slamet Riyadi, 2017)
The objectives of research were: To know the significance of the partially effect ofproduct quality, price, location and customer satisfaction on purchasing decisions atJodho Bekonang Mojolaban food stall. To know customer satisfaction in moderating theeffect of product quality, price and location on purchasing decisions at Jodho BekonangMojolaban food stall. Research method using a survey method, the types data used werequalitative data and quantitative data, the data sources employed were primary data andsecondary data. The population of this research was customers at Jodho BekonangMojolaban food stall. The total samples of this research were 100 respondents, withpurposive sampling as the technique of sampling used. Data methods used werequestionnaire, observation, and documentation. Techniques of analyzing data used werevalidity test, reliability test, classic assumption test, multiple linear regression analysisand absolute difference value test. The result of research, showed that: There was asignificant effect of product quality, price, location and customer satisfaction partiallyon purchasing decisions at Jodho Bekonang Mojolaban food stall. Customer satisfactionmoderate the effect of product quality on purchasing decisions at Jodho BekonangMojolaban food stall. Customer satisfaction does not moderate the effect of price andlocation on purchasing decisions at Jodho Bekonang Mojolaban food stall.Keywords: product quality, price, location, customer satisfaction, purchasing decisions.